The Development of Interactive Learning Media with MIT APP INVENTOR on the Sub-material about the Distribution of Mining Goods in Indonesia - Monassa, Indhit Indari; Handoyo, Budi; Aatuti, Ike Sari (Eastasouth Institute, 2024)
The development of technology is currently growing rapidly followed by other developments. One of which is in the education field which is progressively integrated with technology. The implementation of education which is integrated with technology has been widely found, one of which is in geography subject. This is supported by the increased use of smartphone for learning. Android as smartphone operating system is chosen because it has the advantage of being open source, so it can produce interactive learning media focusing on the learning. The objective of this research is to produce an interactive learning medium with MIT App Inventor platform on the sub-material about the distribution of mining goods in Indonesia. This research used ADDIE method consisting of needs analysis and problem identification, designing android-based interactive learning media designs, producing android-based interactive learning media designs, conducting experts’ validation and conducting trials. Validation was assessed by two experts, namely media and material experts. Meanwhile, trials were conducted individually (teacher) and collectively (students). The results of this study show that this media obtains 98% from a media expert, 82% from a material expert, 88% from individual trial by the teacher and 89% from small groups trial by the students. Overall, this study denotes that this media is classified as highly feasible to be implemented in learning.